Preimplantation Genetic Diagnosis in Clinical Practice - El-Toukhy, Tarek; Braude, Peter; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
This unique book offers a comprehensive yet practical user-friendly guide to preimplantation genetic diagnosis (PGD). It provides understanding of and insight into the complete procedure, its recent clinical and laboratory developments and its future prospects, whilst offering an easy point of reference for patient enquiries. Concluding with perspectives on the ethical and social issues often encountered by healthcare professionals counselling patients with regards to PGD. Each chapter within Preimplantation Genetic Diagnosis in Clinical Practice is written by established authorities in their fields.  An essential resource for PGD specialists and non-specialists, and for all practitioners working within the disciplines of fertility, reproductive medicine and medical genetics.
Introduction -- Basic Genetics for PGD -- Genetic counselling and its role in PGD -- Complex issues in PGD -- Assisted Reproductive Care for PGD Patients -- Embryology and PGD -- PGD for sex-determination and chromosome rearrangements: FISH and emerging technologies -- PGD analysis of embryos for monogenic disorders -- Managing the PGD cycle -- Training and Accreditation in PGD -- PGD data in the UK and Europe -- PGD Facts and Figures -- Pre-implantation diagnosis and HLA-typing: the potential for selection of unaffected HLA matched siblings -- PGD and human embryonic stem cell technology -- Ethical and Social aspects of PGD -- Preimplantation Genetic screening -- Regulation of PGD in the UK and Worldwide -- New Developments in PGD -- The Future of Preimplantation Genetic Testing.
Keywords: Reproductive medicine; Obstetrics; Maternal and child health services; Practice of medicine; Reproductive Medicine; Obstetrics/Perinatology/Midwifery.; Maternal and Child Health; Practice and Hospital Management